A glycolytic burst drives glucose induction of global histone acetylation by picNuA4 and SAGA - Friis, R. Magnus N. (Oxford University Press, 2009)
Little is known about what enzyme complexes or mechanisms control global lysine acetylation in the amino-terminal tails of the histones. Here, we show that glucose induces overall acetylation of H3 K9, 18, 27 and H4 K5, 8, 12 in quiescent yeast cells mainly by stimulating two KATs, Gcn5 and Esa1. Genetic and pharmacological perturbation of carbon metabolism, combined with (1)H-NMR metabolic profiling, revealed that glucose induction of KAT activity directly depends on increased glucose catabolism. Glucose-inducible Esa1 and Gcn5 activities predominantly reside in the picNuA4 and SAGA complexes, respectively, and act on chromatin by an untargeted mechanism. We conclude that direct metabolic regulation of globally acting KATs can be a potent driving force for reconfiguration of overall histone acetylation in response to a physiological cue.